(untitled) (Alexandria, VA, 2003)
Based on the Water Environment Federation's MOP 8 - Design of Municipal Wastewater Treatment Plants, which is the industry standard for wastewater treatment design, this new edition incorporates the latest design concepts and is written from both a theoretical and practical basis. Whether you are a consultant or a utility engineer, this title will 'walk' you through the design process using practical examples, and providing you an education rather than training. Real-life design experience and contemporary theory combine to bring you a deeper understanding of the design process
Keywords: Sewage disposal plants,Sewage,Sewage sludge,Thiết kế và xây dựng hệ thống cấp thoát nước,Cống thoát nước; Design and construction,Purification